Low-viscosity solvent-free epoxy resin cementing material as well as preparation method and application thereof
Through solvent-free modified epoxy resin gelling materials, the problem of difficult sealing of cement ring micro-angle gaps and micro-cracks in oil and gas wells is solved, and the gelling materials with low viscosity, high strength and wide temperature range are achieved to meet the ultra-deep wells of deep wells The sealing requirement improves the integrity of the wellbore seal.
Patent Information
- Application Number
- CN202310795544.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-06-30
AI Technical Summary
The existing technology is difficult to effectively solve the sealing problems of cement ring micro-annular gaps and micro-cracks in oil and gas wells, resulting in the annular belt pressure problem. The traditional resin-based gelling materials have high viscosity, short thickening time and narrow applicable temperature range, which cannot be met. Complex working conditions requirements for deep wells ultra-deep wells.
Use solvent-free modified epoxy resin gelling material to adjust the viscosity and strength by combining curing agent and viscosity adjusting agent, reduce the viscosity of the material, expand the applicable temperature range, improve the compressive strength and elastic modulus after curing, and enhance the cement Sealing capability of ring microcracks.
A gelling material with low viscosity, wide temperature range, high strength and low elastic modulus can effectively seal the micro-angle gaps and micro-cracks of cement rings, improve the seal integrity of the wellbore throughout the life cycle, and is suitable for rings under complex working conditions. Air belt compression control.
Smart Images

Figure CN119220050A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of oil and gas well drilling and completion and downhole maintenance, and relates to a low-viscosity solvent-free epoxy resin gelling material and a preparation method and application thereof. Background Art
[0002] As my country's energy demand continues to increase, the exploration and development of oil and gas resources has gradually moved towards deep and ultra-deep layers, natural gas and unconventional energy. The number of natural gas wells and deep and ultra-deep wells is increasing day by day. At the same time, unconventional oil and gas wells such as gas storage wells and carbon dioxide storage (CCUS) wells have also developed rapidly. Various oil and gas wells face a variety of downhole environments, including complex underground working conditions, high formation pressure, easy gas escape, and acid gas (hydrogen sulfide, carbon dioxide) corrosion. These problems lead to the generation of micro-annular gaps at the cement ring interface and micro-cracks in the cement ring body, which reduces the sealing ability of the cement ring, leading to the increasingly prominent annular pressure problem, posing a severe challenge to the sealing integrity of the wellbore.
[0003] Annular pressure will have many adverse effects on oil and gas wells. Severe annular pressure problems not only affect the safe extraction of oil and gas, but also may lead to safety accidents such as blowouts if they cannot be effectively controlled. Therefore, it is very necessary to control the annular pressure of oil and gas wells, and it is urgent to build a new type of cementitious sealing material system to improve the sealing ability of the wellbore throughout its life cycle. At present, the research on annular pressure control mainly focuses on expansion packers, the construction of self-healing cement slurry systems, and the optimization of cementing processes. Traditional cement slurries contain a large amount of solid particles, which are difficult to squeeze into the micro-annulus and micro-cracks of the cement ring, and the plugging strength cannot meet the long-term sealing requirements, and it is impossible to form an efficient plugging cementitious material system. Therefore, domestic and foreign researchers are committed to developing new wellbore plugging materials to improve the sealing effect of micro-annuli and micro-cracks of the cement ring.
[0004] Since resin materials have the characteristics of good fluidity, strong micro-annulus injection ability, high compressive strength, good toughness, etc., they have gradually become a good alternative for plugging oil and gas wells. CN 110016327 A discloses an oil and gas well plugging material, which is composed of bisphenol A epoxy resin, phenolic epoxy resin, viscosity regulator, curing agent and accelerator, with a thickening time of 120-260min and a compressive strength of 65-87.5MPa. However, this technology needs to be cured at 60-80℃, and the applicable temperature range is relatively narrow. At the same time, the viscosity value of the plugging material is not described, and it is impossible to judge the sealing ability of the material for cement ring micro-annulus and microcracks. Zhao Qingchen et al. prepared bisphenol A epoxy resin DGEBA using epoxy resin, viscosity adjuster and curing agent as raw materials. The curing time of DGEBA is adjustable within 3-6 hours, the compressive strength of the cured body is greater than 40MPa, and the plugging pressure exceeds 30MPa, which meets the requirements for shallow casing plugging. However, only materials suitable for one temperature environment have been developed, the applicable temperature range is small, and the curing time needs to be further improved to extend the on-site construction time. At this stage, the material cannot adapt to the complex working conditions of different regions and wells.
[0005] Although the existing technologies represented by the above-mentioned patents and documents have developed new resin-based gelling sealing materials with plugging capabilities, there are still certain problems with resin-based gelling sealing materials: first, the viscosity of the resin-based gelling sealing materials needs to be further reduced to enhance the ability of the sealing materials to enter the micro-annular gaps and micro-cracks of the cement ring; second, the comprehensive performance of the thickening time of the gelling materials needs to be improved to extend the on-site construction performance of the gelling sealing materials; third, the compressive strength and elastic modulus of the gelling sealing materials after curing need to be further optimized to meet the requirements of the wellbore integrity of oil and gas wells under different complex working conditions.
[0006] Therefore, in order to solve the annulus pressure problem of complex oil and gas wells such as natural gas wells, gas storage wells and CCUS wells, ensure the bonding quality of cement ring interface, and improve the long-term sealing ability of wellbore, it is of great significance to develop a new type of low-viscosity solvent-free epoxy resin cementitious material. Summary of the invention
[0007] In view of the deficiencies in the prior art, the object of the present invention is to provide a low-viscosity solvent-free epoxy resin gelling material and a preparation method and application thereof.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] In one aspect, the present invention provides a solvent-free epoxy resin gelling material, wherein the solvent-free epoxy resin gelling material comprises the following components in parts by weight:
[0010]
[0011] The solvent-free epoxy resin cementitious material of the present invention uses a solvent-free modified epoxy resin to reduce the viscosity of the material, and a curing agent and a viscosity regulator are used in combination to synergistically adjust the viscosity and strength of the cementitious material, so that the obtained cementitious material has a viscosity of 50-800 mPa·s, a wide applicable temperature range (20-90° C.), and has the characteristics of high strength and low elastic modulus. After curing, the 24h compressive strength is greater than 16 MPa, the 48h compressive strength is greater than 35 MPa, and the 24h elastic modulus is less than 5 GPa. It has excellent mechanical properties, good toughness, and good sealing ability for cement ring microcracks. It can meet the annulus pressure management needs under complex working conditions such as deep wells and ultra-deep wells, complex natural gas wells, gas storage wells, and CCUS wells, and effectively ensure the sealing integrity of the wellbore throughout its life cycle.
[0012] Preferably, the solvent-free modified epoxy resin is one or a combination of at least two of bisphenol A type E-51 epoxy resin or E-44 epoxy resin modified with a reactive diluent. The use of solvent-free modified epoxy resin makes the material have the characteristics of low viscosity and stable performance.
[0013] Preferably, the active diluent is selected from any one of alkylene glycidyl ether, butyl glycidyl ether, 1,4-butanediol diglycidyl ether, ethylene glycol diglycidyl ether, phenyl glycidyl ether, neopentyl glycol diglycidyl ether, and polypropylene glycol diglycidyl ether, or a combination of at least two thereof.
[0014] Preferably, the curing agent is selected from any one of aliphatic polyprimary amines, aromatic polyprimary amines, polyamides, polythiols or polyacid anhydrides, or a combination of at least two thereof, preferably aliphatic polyprimary amines.
[0015] Preferably, the aliphatic polyamine is selected from any one of diethylenetriamine, triethylenetetramine, tetraethylenepentamine, N,N-diethylaminopropylamine, and caprylamide diamine, or a combination of at least two thereof;
[0016] Preferably, the aromatic polyvalent primary amine is selected from any one or a combination of at least two of m-phenylenediamine, 4,4-diaminodiphenylmethane, 4,4-diaminodiphenyl sulfone or m-phenylenediamine;
[0017] Preferably, the polyacid anhydride includes but is not limited to any one of phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, nadic methyl anhydride, chlorendic anhydride or pyromellitic anhydride, or a combination of at least two thereof.
[0018] In the present invention, the amount of the curing agent is 5 parts by weight, 8 parts by weight, 10 parts by weight, 20 parts by weight, 30 parts by weight, 40 parts by weight, 50 parts by weight, 60 parts by weight, 70 parts by weight or 80 parts by weight.
[0019] Preferably, the viscosity modifier is a viscosity modifier containing epoxy groups and / or benzene rings. Such a viscosity modifier has good curing activity. Preferably, the viscosity modifier is selected from any one of phenyl glycidyl ether, benzyl glycidyl ether, cashew phenol aldehyde hydroglycerol ether or epoxy soybean oil, or a combination of at least two thereof.
[0020] In the present invention, the viscosity adjusting agent is used in an amount of 5 parts by weight, 8 parts by weight, 10 parts by weight, 20 parts by weight, 30 parts by weight or 40 parts by weight.
[0021] Preferably, the curing regulator is selected from any one or a combination of at least two of triethylamine, triethanolamine, o-hydroxybenzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, benzyldimethylamine, N-(2-hydroxyphenyl)-N',N'-dimethylurea, phenol, resorcinol, o-cresol, nonylphenol, boron trifluoride complex, tertiary amine, imidazoles or acetylacetone metal salts.
[0022] In the present invention, the amount of the curing regulator is 0.2 parts by weight, 0.5 parts by weight, 1 part by weight, 2 parts by weight, 3 parts by weight, 4 parts by weight or 5 parts by weight.
[0023] Preferably, the toughening material is selected from any one or a combination of at least two of cage-type polysilsesquioxane (POSS), nano-silica, micro-silicon, hollow glass micro-beads or floating beads, and the cage-type polysilsesquioxane (POSS) includes but is not limited to octacyclohexylethyl-POSS, glycidyloxypropyl-POSS, glycidyloxypropylcyclotetrasiloxane, octaphenyl-POSS, octaoctyl-POSS, dimethylsiloxy-POSS or octaanilinepropyl-POSS.
[0024] In the present invention, the amount of the toughening material is 0 parts by weight, 1 part by weight, 3 parts by weight, 5 parts by weight, 8 parts by weight, 10 parts by weight, 12 parts by weight, 15 parts by weight, 18 parts by weight or 20 parts by weight.
[0025] Preferably, the defoamer is selected from polyether defoamers, silicone defoamers and modified materials thereof, including but not limited to polysiloxane, modified polysiloxane, polyether-modified silicone, and hydroxypolydimethylsiloxane;
[0026] In the present invention, the defoaming agent is used in an amount of 0.1 parts by weight, 0.3 parts by weight, 0.5 parts by weight, 0.8 parts by weight or 1 part by weight.
[0027] The solvent-free epoxy resin gelling material of the present invention can be used in an environment of 20-90°C (e.g., 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 60°C, 70°C, 80°C or 90°C).
[0028] On the other hand, the present invention provides a method for preparing the solvent-free epoxy resin gelling material as described above, the preparation method comprising the following steps:
[0029] The solvent-free modified epoxy resin, curing agent, viscosity adjusting agent, curing regulator, toughening material and defoaming agent are mixed to obtain the solvent-free epoxy resin gelling material.
[0030] Preferably, the mixing is carried out at a rotation speed of 200-1000 r / min (e.g., 200 r / min, 230 r / min, 250 r / min, 300 r / min, 400 r / min, 500 r / min, 600 r / min, 700 r / min, 800 r / min, 900 r / min or 1000 r / min).
[0031] Preferably, the mixing time is 5-20 min, for example 5 min, 8 min, 10 min, 12 min, 15 min, 18 min or 20 min.
[0032] On the other hand, the present invention provides an oil and gas well plugging material, wherein the oil and gas well plugging material comprises the solvent-free epoxy resin gelling material as described above.
[0033] On the other hand, the present invention provides the use of the solvent-free epoxy resin gelling material or oil and gas well plugging material as described above in the exploration and development of oil and gas resources.
[0034] The low-viscosity solvent-free epoxy resin gelling material of the present invention is suitable for the annular pressure management under complex working conditions such as complex natural gas wells, gas storage wells, CCUS wells, etc., and the plugging of cement ring micro-annuluses and micro-cracks.
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] The solvent-free epoxy resin gelling material of the present invention has a low viscosity (50-800mPa·s), a wide applicable temperature range (20-90°C), and the characteristics of high strength and low elastic modulus. After curing, the compressive strength is greater than 16MPa for 24h, the compressive strength is greater than 35MPa for 48h, the compressive strength can reach up to 95MPa, and the elastic modulus is less than 5GPa for 24h. It has excellent mechanical properties, good toughness, good corrosion resistance, aging resistance and other capabilities, and has good sealing ability for cement ring microcracks. It can meet the annular pressure management requirements under complex working conditions such as deep wells, ultra-deep wells, complex natural gas wells, gas storage wells, and CCUS wells, and efficiently ensures the sealing integrity of the wellbore throughout its life cycle. The preparation method is simple, green and environmentally friendly, the raw materials are widely available, the cost is low, and it has the potential for large-scale production. It can be applied to a variety of complex working conditions, can meet the technical requirements of annular pressure management of complex wells such as natural gas wells, gas storage wells, and CCUS wells, and has a broad application market. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a curve diagram showing the relationship between the thickening time, 24h compressive strength and the amount of curing agent added of the epoxy resin gelling material system at 90°C in Example 1.
[0038] Figure 2 This is a curve diagram showing the relationship between the thickening time, 24h compressive strength and the amount of curing regulator added of the epoxy resin gelling material system at 60°C in Example 2. DETAILED DESCRIPTION
[0039] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0040] In this specification, unless otherwise specified, the terms used herein should be understood as the meanings commonly used in the field. If there is a conflict, the present specification shall prevail.
[0041] In this specification, unless otherwise specified, various raw materials used in the present invention can be purchased or prepared by existing methods, and the instruments and equipment used in the present invention can be purchased.
[0042] The test method of the present invention and the equipment used in the test are as follows:
[0043] (1) The compressive strength of the sample after the cementitious material is cured is determined according to the test method specified in GB / T19139-2012 "Test Methods for Oil Well Cement". The test instrument is an oil well cement compressive strength tester.
[0044] (2) The method for determining the thickening time of cementitious materials is to be tested according to the experimental method specified in GB / T19139-2012 "Test methods for oil well cement".
[0045] (3) The viscosity was measured according to GB / T10247-2008 "Viscosity Measurement Method". The test instrument was a Brookfield viscometer from the United States.
[0046] (4) The elastic modulus of the samples after curing of cementitious materials under different curing conditions (temperature, time) was tested using a cement paste triaxial test system.
[0047] In addition to the above, according to the curing characteristics of the resin material, the epoxy resin gelling material of the present invention is optimized by system design parameters.
[0048] In addition, according to the curing mechanism, the viscosity and thickening time of the gelling material of the present invention can be regulated by optimizing system parameters, thereby meeting the personalized needs of different temperatures and different working conditions.
[0049] Example 1
[0050] Weigh 100 parts by weight of a solvent-free epoxy resin, add 30 parts by weight of a curing agent, 30 parts by weight of a viscosity regulator, 0.5 parts by weight of a curing regulator, and 0.5 parts by weight of a defoaming agent in sequence under stirring, and mix the above raw materials evenly at a drilling speed of 500 r / min to obtain a solvent-free epoxy resin gelling material, wherein the solvent-free epoxy resin is a modified low-viscosity solvent-free epoxy resin purchased from Baling Petrochemical, model CYDW-100, the curing agent is a modified fatty amine purchased from Fujian Wangpai New Materials Co., Ltd., model Kingcure 305LC, the viscosity regulator is epoxy soybean oil, the curing regulator is 2,4,6-tris(dimethylaminomethyl)phenol, and the defoaming agent is a mixture of polyether and silicone (mixing ratio is 1:1), purchased from Dongguan Defeng Defoaming Agent Co., Ltd., model DF-103.
[0051] The viscosity, thickening time, compressive strength and elastic modulus of the cementitious material were measured: at 25°C, the viscosity of the cementitious material was 386 mPa·s; at 90°C water bath normal pressure curing environment, the 24h compressive strength of the cementitious material was 55.6 MPa, the 48h compressive strength was 82.3 MPa, and the 24h elastic modulus was 3.5 GPa; at 90°C normal pressure thickening environment, the thickening time of the cementitious material was 240 min. This shows that the cementitious material can ensure smooth construction and cement ring sealing effect.
[0052] Embodiment 2:
[0053] Weigh 100 parts by weight of a solvent-free epoxy resin, add 20 parts by weight of a curing agent, 30 parts by weight of a viscosity regulator, 0.5 parts by weight of a curing regulator, and 1 part by weight of a defoamer in sequence under stirring, and mix the above raw materials evenly at a drilling speed of 500 r / min to obtain a solvent-free epoxy resin gelling material, wherein the solvent-free epoxy resin is a modified low-viscosity solvent-free epoxy resin purchased from Baling Petrochemical, model CYDW-100, the curing agent is a modified fatty amine purchased from Fujian Wangpai New Materials Co., Ltd., model Kingcure 305LC, the viscosity regulator is epoxy soybean oil, the curing regulator is 2,4,6-tris(dimethylaminomethyl)phenol, and the defoamer is a mixture of polyether and silicone (mixing ratio is 1:1), purchased from Dongguan Defeng Defoamer Co., Ltd., model DF-103.
[0054] The viscosity, thickening time, compressive strength and elastic modulus of the cementitious material were measured: at 25°C, the viscosity of the cementitious material was 475 mPa·s; at 80°C water bath normal pressure curing environment, the 24h compressive strength of the cementitious material was 42.5 MPa, the 48h compressive strength was 76.4 MPa, and the 24h elastic modulus was 3.1 GPa; at 80°C normal pressure thickening environment, the thickening time of the cementitious material was 330 min. This shows that the cementitious material can ensure smooth construction and cement ring sealing effect.
[0055] Embodiment 3:
[0056] Weigh 100 parts by weight of a solvent-free epoxy resin, add 40 parts by weight of a curing agent, 30 parts by weight of a viscosity regulator, 0.5 parts by weight of a curing regulator, and 0.5 parts by weight of a defoaming agent in sequence under stirring, and mix the above raw materials evenly at a drilling speed of 500 r / min to obtain a solvent-free epoxy resin gelling material, wherein the solvent-free epoxy resin is a modified low-viscosity solvent-free epoxy resin purchased from Baling Petrochemical, model CYDW-100, the curing agent is a modified fatty amine purchased from Fujian Wangpai New Materials Co., Ltd., model Kingcure 305LC, the viscosity regulator is epoxy soybean oil, the curing regulator is 2,4,6-tris(dimethylaminomethyl)phenol, and the defoaming agent is a mixture of polyether and silicone (mixing ratio is 1:1), purchased from Dongguan Defeng Defoaming Agent Co., Ltd., model DF-103.
[0057] The viscosity, thickening time, compressive strength and elastic modulus of the cementitious material were measured: at 25°C, the viscosity of the cementitious material was 315 mPa·s; at 90°C water bath normal pressure curing environment, the 24h compressive strength of the cementitious material was 37.6 MPa, and the 24h elastic modulus was 2.5 GPa; at 90°C normal pressure thickening environment, the thickening time of the cementitious material was 180 min. This shows that the cementitious material can ensure smooth construction and cement ring sealing effect.
[0058] Embodiment 4:
[0059] Weigh 100 parts by weight of solvent-free epoxy resin, add 30 parts by weight of curing agent, 20 parts by weight of viscosity regulator, 0.5 parts by weight of curing regulator, 0.5 parts by weight of defoaming agent, and 5 parts by weight of toughening material in sequence under stirring, mix the above raw materials evenly at a drilling speed of 500 r / min to obtain a solvent-free epoxy resin gelling material, wherein the solvent-free epoxy resin is a modified low-viscosity solvent-free epoxy resin purchased from Baling Petrochemical, model CYDW-100, and the curing agent is a modified fatty amine purchased from Fujian Kingcure New Materials Co., Ltd., model Kingcure 305LC, the viscosity regulator is benzyl glycidyl ether, the curing regulator is 2,4,6-tris(dimethylaminomethyl)phenol, the defoamer is a mixture of polyether and silicone (mixing ratio is 1:1), purchased from Dongguan Defeng Defoamer Co., Ltd., model DF-103, and the toughening material is octaepoxycyclohexylethyl-POSS.
[0060] The viscosity, thickening time, compressive strength and elastic modulus of the cementitious material were measured: at 25°C, the viscosity of the cementitious material was 120 mPa·s; at 90°C water bath normal pressure curing environment, the 24h compressive strength of the cementitious material was 21.2 MPa, and the 24h elastic modulus was 2.3 GPa; at 90°C normal pressure thickening environment, the thickening time of the cementitious material was 160 min. This shows that the cementitious material can ensure smooth construction and cement ring sealing effect.
[0061] Embodiment 5:
[0062] Weigh 100 parts by weight of solvent-free epoxy resin, add 30 parts by weight of curing agent, 40 parts by weight of viscosity regulator, 1.0 parts by weight of curing regulator, 0.5 parts by weight of defoaming agent, and 5 parts by weight of toughening material in sequence under stirring, mix the above raw materials evenly at a drilling speed of 500 r / min to obtain a solvent-free epoxy resin gelling material, wherein the solvent-free epoxy resin is a modified low-viscosity solvent-free epoxy resin purchased from Baling Petrochemical, model CYDW-100, and the curing agent is a modified fatty amine purchased from Fujian Kingcure New Materials Co., Ltd., model Kingcure 305LC, the viscosity regulator is benzyl glycidyl ether, the curing regulator is 2,4,6-tris(dimethylaminomethyl)phenol, the defoamer is a mixture of polyether and silicone (mixing ratio is 1:1), purchased from Dongguan Defeng Defoamer Co., Ltd., model DF-103, and the toughening material is glycidyl ether oxypropyl-POSS.
[0063] The viscosity, thickening time, compressive strength and elastic modulus of the cementitious material were measured: at 25°C, the viscosity of the cementitious material was 50 mPa·s; at 90°C water bath normal pressure curing environment, the 24h compressive strength of the cementitious material was 20.2 MPa, and the 24h elastic modulus was 2.1 GPa; at 90°C normal pressure thickening environment, the thickening time of the cementitious material was 240 min. This shows that the cementitious material can ensure smooth construction and cement ring sealing effect.
[0064] Embodiment 6:
[0065] Weigh 100 parts by weight of solvent-free epoxy resin, add 20 parts by weight of curing agent, 30 parts by weight of viscosity regulator, 1.0 parts by weight of curing regulator, 0.5 parts by weight of defoaming agent, and 5 parts by weight of toughening material in sequence under stirring, mix the above raw materials evenly at a drilling speed of 500 r / min to obtain a solvent-free epoxy resin gelling material, wherein the solvent-free epoxy resin is a modified low-viscosity solvent-free epoxy resin purchased from Baling Petrochemical, model CYDW-100, and the curing agent is a modified fatty amine purchased from Fujian Kingcure New Materials Co., Ltd., model Kingcure 305LC, the viscosity regulator is benzyl glycidyl ether, the curing regulator is 2,4,6-tris(dimethylaminomethyl)phenol, the defoamer is a mixture of polyether and silicone (mixing ratio is 1:1), purchased from Dongguan Defeng Defoamer Co., Ltd., model DF-103, and the toughening material is glycidyl ether oxypropyl-POSS.
[0066] The viscosity, thickening time, compressive strength and elastic modulus of the cementitious material were measured: at 25°C, the viscosity of the cementitious material was 109 mPa·s; at 90°C water bath normal pressure curing environment, the 24h compressive strength of the cementitious material was 16.8 MPa, and the 24h elastic modulus was 1.9 GPa; at 90°C normal pressure thickening environment, the thickening time of the cementitious material was 296 min. This shows that the cementitious material can ensure smooth construction and cement ring sealing effect.
[0067] Embodiment 7:
[0068] Weigh 100 parts by weight of a solvent-free epoxy resin, add 60 parts by weight of a curing agent, 3.0 parts by weight of a curing regulator, and 0.5 parts by weight of a defoaming agent in sequence under stirring, and mix the above raw materials evenly at a drilling speed of 500 r / min to obtain a solvent-free epoxy resin gelling material, wherein the solvent-free epoxy resin is a modified low-viscosity solvent-free epoxy resin purchased from Baling Petrochemical, model CYDW-100, the curing agent is a modified fatty amine purchased from Fujian Wangpai New Materials Co., Ltd., model Kingcure 305LC, the curing regulator is 2,4,6-tris(dimethylaminomethyl)phenol, and the defoaming agent is a mixture of polyether and silicone (mixing ratio of 1:1), purchased from Dongguan Defeng Defoaming Agent Co., Ltd., model DF-103.
[0069] The viscosity, thickening time and compressive strength of the cementitious material were measured: at 25°C, the viscosity of the cementitious material was 324 mPa·s; at 25°C water bath normal pressure curing environment, the 24h compressive strength of the cementitious material was 21.3 MPa, and the 48h compressive strength was 33.6 MPa; at 25°C normal pressure thickening environment, the thickening time of the cementitious material was 420 min. This shows that the cementitious material can ensure smooth construction and cement ring sealing effect.
[0070] Comparative Example 1:
[0071] The same method as in Example 1 was used, except that the epoxy resin was replaced with conventional E-51 epoxy resin.
[0072] 100 parts by weight of epoxy resin were weighed, and 30 parts by weight of curing agent, 30 parts by weight of viscosity regulator, 0.5 parts by weight of curing regulator and 0.5 parts by weight of defoaming agent were added in sequence under stirring. The above raw materials were mixed evenly at a drilling speed of 500 r / min to obtain an epoxy resin gelling material, wherein the curing agent was a modified fatty amine purchased from Fujian Kingcure New Materials Co., Ltd., model Kingcure 305LC, the viscosity regulator was epoxy soybean oil, the curing regulator was 2,4,6-tris(dimethylaminomethyl)phenol, and the defoaming agent was a mixture of polyether and silicone (mixing ratio was 1:1), purchased from Dongguan Defeng Defoaming Agent Co., Ltd., model DF-103.
[0073] The viscosity, thickening time, compressive strength and elastic modulus of the cementitious material were measured: at 25°C, the viscosity of the cementitious material was 3236 mPa·s; at 90°C water bath normal pressure curing environment, the 24h compressive strength of the cementitious material was 65.4 MPa, and the 24h elastic modulus was 4.6 GPa; at 90°C normal pressure thickening environment, the thickening time of the cementitious material was 190 min. This shows that the cementitious material based on the unmodified conventional E-51 epoxy resin has a high viscosity and cannot meet the requirements of on-site pumping and injection into cement ring microcracks. And the elastic toughness is poor after curing.
[0074] Comparative Example 2:
[0075] The method is as in Example 4, except that no viscosity adjusting agent is used and the amount of curing agent used is the sum of the amounts of the viscosity adjusting agent and the curing agent used in Example 4.
[0076] Weigh 100 parts by weight of a solvent-free epoxy resin, add 50 parts by weight of a curing agent, 0.5 parts by weight of a curing regulator, 0.5 parts by weight of a defoaming agent, and 5 parts by weight of a toughening material in sequence under stirring, and mix the above raw materials evenly at a drilling speed of 500 r / min to obtain a solvent-free epoxy resin gelling material, wherein the solvent-free epoxy resin is a modified low-viscosity solvent-free epoxy resin purchased from Baling Petrochemical, model CYDW-100, the curing agent is a modified fatty amine purchased from Fujian Wangpai New Materials Co., Ltd., model Kingcure 305LC, the curing regulator is 2,4,6-tris(dimethylaminomethyl)phenol, the defoaming agent is a mixture of polyether and silicone (mixing ratio of 1:1), purchased from Dongguan Defeng Defoaming Agent Co., Ltd., model DF-103, and the toughening material is octaepoxycyclohexylethyl-POSS.
[0077] The viscosity, thickening time, compressive strength and elastic modulus of the cementitious material were measured: at 25°C, the viscosity of the cementitious material was 458 mPa·s; under 90°C water bath normal pressure curing environment, the 24h compressive strength of the cementitious material was 28.4 MPa, and the 24h elastic modulus was 2.8 GPa; under 90°C normal pressure thickening environment, the thickening time of the cementitious material was 105 min. The thickening time of the cementitious material is short and cannot meet the construction requirements. This shows that the viscosity regulator plays an important role in the cementitious material. First, it can reduce the viscosity of the cementitious material, making it easier to pump and inject into microcracks; second, it can prolong the thickening time and improve the on-site construction performance.
[0078] Comparative Example 3
[0079] The method is as in Example 4, except that no curing agent is used and the amount of the viscosity adjusting agent used is the sum of the amounts of the viscosity adjusting agent and the curing agent used in Example 4.
[0080] Weigh 100 parts by weight of a solvent-free epoxy resin, and add 0.5 parts by weight of a curing regulator, 50 parts by weight of a viscosity regulator, 0.5 parts by weight of a defoamer, and 5 parts by weight of a toughening material in sequence under stirring. The above raw materials are evenly mixed at a drilling speed of 500 r / min to obtain a solvent-free epoxy resin gelling material, wherein the solvent-free epoxy resin is a modified low-viscosity solvent-free epoxy resin purchased from Baling Petrochemical, model CYDW-100, the viscosity regulator is benzyl glycidyl ether, the curing regulator is 2,4,6-tris(dimethylaminomethyl)phenol, the defoamer is a mixture of polyether and silicone (mixing ratio of 1:1), purchased from Dongguan Defeng Defoamer Co., Ltd., model DF-103, and the toughening material is octaepoxycyclohexylethyl-POSS.
[0081] The viscosity, thickening time and compressive strength of the cementitious material were measured: at 25°C, the viscosity of the cementitious material was 365 mPa·s; under 90°C water bath normal pressure curing environment, the cementitious material was in a fluid state for 24 hours and had no strength; under 90°C normal pressure thickening environment, the cementitious material could not solidify.
[0082] Comparative Example 4:
[0083] As in Example 3, except that no cure modifier was used.
[0084] Weigh 100 parts by weight of a solvent-free epoxy resin, add 40 parts by weight of a curing agent, 30 parts by weight of a viscosity regulator, and 0.5 parts by weight of a defoamer in sequence under stirring, and mix the above raw materials evenly at a drilling speed of 500 r / min to obtain a solvent-free epoxy resin gelling material, wherein the solvent-free epoxy resin is a modified low-viscosity solvent-free epoxy resin purchased from Baling Petrochemical, model CYDW-100, the curing agent is a modified fatty amine purchased from Fujian Wangpai New Materials Co., Ltd., model Kingcure 305LC, the viscosity regulator is epoxy soybean oil, and the defoamer is a mixture of polyether and silicone (mixing ratio of 1:1), purchased from Dongguan Defeng Defoamer Co., Ltd., model DF-103.
[0085] The viscosity, thickening time, compressive strength and elastic modulus of the cementitious material were measured: at 25°C, the viscosity of the cementitious material was 317 mPa·s; under 90°C water bath normal pressure curing environment, the 24h compressive strength of the cementitious material was 0 MPa, and the 48h compressive strength was 1.5 MPa; under 90°C normal pressure thickening environment, the thickening time of the cementitious material exceeded 24h.
[0086] In summary, the low-viscosity solvent-free epoxy resin cementitious material of the present invention has excellent comprehensive performance. The viscosity, applicable temperature and thickening time of the cementitious material can be regulated by means of optimizing the external additives and optimizing the system parameters. It has good on-site construction performance, meets the requirements of domestic natural gas wells, gas storage wells and CCUS wells for cement ring sealing ability, can effectively seal the micro-annulus and micro-cracks of the cement ring, improve the sealing integrity of the wellbore, and efficiently control the annulus pressure problem.
[0087] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the solvent-free epoxy resin gelling material and its preparation method and application, but the present invention is not limited to the above-mentioned embodiments, that is, it does not mean that the present invention must rely on the above-mentioned embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A solvent-free epoxy resin gelling material, characterized in that: The solvent-free epoxy resin gelling material comprises the following components in parts by weight:
2. The solvent-free epoxy resin gelling material according to claim 1, characterized in that: The solvent-free modified epoxy resin is one or a combination of at least two of bisphenol A type E-51 epoxy resin or E-44 epoxy resin modified by using a reactive diluent; Preferably, the active diluent is selected from any one of alkylene glycidyl ether, butyl glycidyl ether, 1,4-butanediol diglycidyl ether, ethylene glycol diglycidyl ether, phenyl glycidyl ether, neopentyl glycol diglycidyl ether, and polypropylene glycol diglycidyl ether, or a combination of at least two thereof.
3. The solvent-free epoxy resin gelling material according to claim 1 or 2, characterized in that: The curing agent is selected from any one of aliphatic polyprimary amines, aromatic polyprimary amines, polyamides, polythiols or polyacid anhydrides, or a combination of at least two thereof, preferably aliphatic polyprimary amines.
4. The solvent-free epoxy resin gelling material according to claim 3, characterized in that: The aliphatic polyamine is selected from any one of diethylenetriamine, triethylenetetramine, tetraethylenepentamine, N,N-diethylaminopropylamine, and caprylamide diamine, or a combination of at least two thereof; Preferably, the aromatic polyamine is selected from any one or a combination of at least two of m-phenylenediamine, 4,4-diaminodiphenylmethane, 4,4-diaminodiphenyl sulfone or m-phenylenediamine; Preferably, the polyacid anhydride includes any one of phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, nadic methyl anhydride, chlorendic anhydride or pyromellitic anhydride, or a combination of at least two thereof.
5. The solvent-free epoxy resin gelling material according to any one of claims 1 to 4, characterized in that: The viscosity modifier is a viscosity modifier containing epoxy groups and / or benzene rings; Preferably, the viscosity adjusting agent is selected from any one of phenyl glycidyl ether, benzyl glycidyl ether, cashew phenol aldehyde hydroglyceryl ether or epoxy soybean oil, or a combination of at least two thereof.
6. The solvent-free epoxy resin gelling material according to any one of claims 1 to 5, characterized in that: The curing regulator is selected from any one of triethylamine, triethanolamine, o-hydroxybenzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, benzyldimethylamine, N-(2-hydroxyphenyl)-N',N'-dimethylurea, phenol, resorcinol, o-cresol, nonylphenol, boron trifluoride complex, tertiary amine, imidazoles or acetylacetone metal salts, or a combination of at least two thereof.
7. The solvent-free epoxy resin gelling material according to any one of claims 1 to 6, characterized in that: The toughening material is selected from any one of cage-type polysilsesquioxane, nano-silica, micro-silicon, hollow glass micro-beads or floating beads, or a combination of at least two thereof. The cage-type polysilsesquioxane includes but is not limited to octa-epoxycyclohexylethyl cage-type polysilsesquioxane, glycidyloxypropyl cage-type polysilsesquioxane, glycidyloxypropyl cyclotetrasiloxane, octaphenyl cage-type polysilsesquioxane, octa-octyl cage-type polysilsesquioxane, dimethylsiloxy cage-type polysilsesquioxane or octaaniline propyl cage-type polysilsesquioxane; Preferably, the defoamer is selected from polyether defoamers, silicone defoamers and modified materials thereof; Preferably, the defoaming agent is selected from any one or a combination of at least two of polysiloxane, modified polysiloxane, polyether-modified silicone or hydroxypolydimethylsiloxane; Preferably, the solvent-free epoxy resin gelling material is used in an environment of 20-90°C.
8. The method for preparing the solvent-free epoxy resin gelling material according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: Mixing a solvent-free modified epoxy resin, a curing agent, a viscosity adjusting agent, a curing regulator, a toughening material and a defoaming agent to obtain the solvent-free epoxy resin gelling material; Preferably, the mixing is carried out at a rotation speed of 200-1000 r / min; Preferably, the mixing time is 5-20 min.
9. An oil and gas well plugging material, characterized in that: The oil and gas well plugging material comprises the solvent-free epoxy resin gelling material according to any one of claims 1 to 7.
10. Use of the solvent-free epoxy resin gelling material according to any one of claims 1 to 7 or the oil and gas well plugging material according to claim 9 in the exploration and development of oil and gas resources.
Citation Information
Patent Citations
Oil-gas well plugging material and production method thereof
CN110016327A
Aqueous modified synergetic resin cementing material as well as preparation method and application thereof
CN110540830A
Epoxy polyhedral oligomeric silsesquioxane toughened epoxy resin and preparation method thereof
CN111875928A
Epoxy resin well cementation plugging system as well as preparation method and application thereof
CN112341999A
Modified resin, application of modified resin in plugging agent, high-temperature plugging agent and application of high-temperature plugging agent in plugging of high-temperature discarded well
CN113637293A
Cited By
INS high-temperature-resistant and scratch-resistant automobile decorative film and preparation method thereof
CN120623920A